2020
DOI: 10.3390/ijms21030898
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of 2-Hydroxypropyl-Cyclodextrins on Lipid Accumulation in Npc1-Null Cells

Abstract: Niemann–Pick disease type C (NPC) is an autosomal recessive disorder characterized by abnormal accumulation of free cholesterol and sphingolipids in lysosomes. The iminosugar miglustat, which inhibits hexosylceramide synthesis, is used for NPC treatment, and 2-hydroxypropyl-β-cyclodextrin (HP-β-CD), a cyclic oligosaccharide derivative, is being developed to treat NPC. Moreover, therapeutic potential of 2-hydroxypropyl-γ-cyclodextrin (HP-γ-CD) was shown in NPC models, although its mechanism of action remains un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 46 publications
(56 reference statements)
0
11
0
Order By: Relevance
“…However, whether cholesterol is the true target molecule of HP-β-CD in the attenuation of NPC disease conditions has remained controversial, and Davidson et al [ 5 ] suggested that HP-β-CD may interact with other NPC disease-related substrates, such as sphingolipids. Indeed, we previously demonstrated that HP-β-CD can significantly attenuate sphingomyelin accumulation in Npc1 -deficient Chinese hamster ovarian cells, as well as the accumulation of free cholesterol [ 24 ]. Marques et al [ 25 ] reported that glucocerebrosidase 2 gene knockout and pharmacological inhibition ameliorated the manifestations of NPC, such as Purkinje cell loss, motor dysfunction, and shortened lifespan, without correcting cholesterol levels, in Npc1 −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether cholesterol is the true target molecule of HP-β-CD in the attenuation of NPC disease conditions has remained controversial, and Davidson et al [ 5 ] suggested that HP-β-CD may interact with other NPC disease-related substrates, such as sphingolipids. Indeed, we previously demonstrated that HP-β-CD can significantly attenuate sphingomyelin accumulation in Npc1 -deficient Chinese hamster ovarian cells, as well as the accumulation of free cholesterol [ 24 ]. Marques et al [ 25 ] reported that glucocerebrosidase 2 gene knockout and pharmacological inhibition ameliorated the manifestations of NPC, such as Purkinje cell loss, motor dysfunction, and shortened lifespan, without correcting cholesterol levels, in Npc1 −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…The existing literature data demonstrate that the γCD derivative HPγCD may act as a therapeutic approach for Niemann-Pick type C disease (NPC) [ 84 , 85 , 86 , 87 , 88 ], which is a fatal neurodegenerative disorder characterized by a massive accumulation of free cholesterol and other lipids in late endosomes and lysosomes. In addition, NPC1-deficient cells showed defects in autophagy [ 89 , 90 ].…”
Section: Application Of Cyclodextrinsmentioning
confidence: 99%
“…However, the underlying mechanism of action remains to be clarified. Hoque et al [ 88 ] showed that both HPβCD and HPγCD (but not HPαCD) reduced cholesterol and sphingolipid accumulation solely in Npc1-null Chinese hamster ovary cells, but not in the corresponding control wild-type cells.…”
Section: Application Of Cyclodextrinsmentioning
confidence: 99%
“…HP-β-CD and HP-γ-CD, unlike HP-α-CD, reduced the level of sphingomyelins in Npc1 -null, but not wild-type, cells. 2-hydroxypropyl-γ-cyclodextrin appears to have therapeutic potential, but more research is needed (Hoque et al 2020 ).…”
Section: Hp-β-cdmentioning
confidence: 99%